Antibodies to voltage-gated calcium channels in children with falciparum malaria. - Lang, B; Newbold, C; Williams, G; Peshu, N; Marsh, K; Newton, C (2005)
Falciparum malaria can affect the central nervous system (CNS), causing neurological dysfunction and sequelae. The pathophysiology of these complications is currently very poorly understood. Production of autoantibodies has frequently been reported as a consequence of infection with Plasmodium falciparum. However, at present, the presence of antibodies to components of the CNS during malaria infection has not been reported. We have sought to identify such antibodies, define their specificity, and determine whether they are involved in the development of neurological complications of falciparum malaria. Here, we show that, in a cohort of Kenyan children, levels of antibodies to the voltage-gated calcium channels, but not to other ion channels, increased with the severity of malaria infection.